(untitled) (Journal of Global Humanities and Social Sciences, 2025)
With the improvement of the territorial spatial planning system and the deepening of ecological civilization construction, territorial spatial ecological restoration has become an important measure to address ecological and environmental problems and ensure ecological security. Taking Hunan Province as the research object, this paper approaches the issue from the perspective of the ecological security pattern, analyzing the current status of ecosystems and the needs for collaborative restoration within the region. It identifies key challenges in the restoration process, such as regional interest conflicts, unbalanced resource allocation, and the absence of collaborative mechanisms. Furthermore, it explores a restoration path of “pattern optimization–zoning collaboration–mechanism guarantee” and proposes targeted regional collaboration strategies. The study aims to provide theoretical references and practical support for improving the efficiency of territorial spatial ecological restoration in Hunan Province, safeguarding regional ecological security, and promoting the synergy between ecological protection and economic development.